Effect of laser irradiation on xanthine oxidase activity and superoxide radical generation in rat liver cytosol fraction - O. V. Ketsa; N. B. Kutsak; M. M. Marchenko (Біологія тварин, 2020)
The effect of tumor growth in the body and laser irradiation on the enzymatic activity of xanthine oxidase, in particular its D- and O-forms, and also the rate of generation of the superoxide radical (O2–) and the level of protein sulfhydryl groups in the liver rat cytosolic fraction has been investigated. It has been found that in the cytosolic fraction of rats with transplanted Guerin’s carcinoma decreases the enzymatic activity of the D-form of xanthine oxidase with a simultaneous increase in its O-form during the period of intensive (14 days, which corresponds to the logarithmic phase of on cogenesis) and the period of final tumor growth (21 days, which corresponds to the stationary phase of oncogenesis). The increase in the enzymatic activity of the O-form of xanthine oxidase was accompanied by an increase the rate of superoxide radical generation and a decrease in the level of protein SH-groups in the liver cytosolic fraction of tumor-bearing rats. Daily directed action of laser irradiation on the area of growth of Guerin’s carcinoma leads to less destructive changes in the liver. Thus, there is an increase in the enzymatic activity of the D-form of xanthine oxidase, a decrease the rate of superoxide radical formation and an increase the content of protein SH-groups in the cytosolic fraction of the liver of experimental animals compared with non-irradiated tumor-bearing rats.